Cassava mosaic disease in South and Southeast Asia: current status and prospects - Hareesh, Padinjarepulikkiyil Sankaran; Resmi, Thulasi Raveendrannair; Sheela, Madhavi N.; Makeshkumar, Thangaraj (Frontiers in Sustainable Food Systems, 2023)
Cassava is one of the most important food and industrial crops in Asia, Africa and South America. Cassava mosaic disease, caused by cassava mosaic geminivirus, is one of the major constraints to cassava cultivation. In Asia the disease is caused by Indian cassava mosaic virus and Sri Lankan cassava mosaic virus. Phytosanitation, vector control, breeding and genetic engineering strategies have been widely adopted to manage the disease. This article is a comprehensive review of the disease spread, development of diagnostic methods and various approaches employed for the management of cassava mosaic disease (CMD) in South and Southeast Asia (SEA).